Agronomic characteristics of sorghum submitted to the seaweed extract application and Azospirillum brasilense through leaf path (Research, Society and Development, 2020)
In the world scenario, biostimulants have been studied in several cultures to verify their possible results in variables related to plant development. With this, this work aimed to evaluate agronomic characteristics of double aptitude sorghum plants submitted to the application of fertilizer with algae extract and Azospirillum brasilense via leaf at 60 days after sowing (DAS). The experiment was conducted at the Teaching, Research and Extension Farm (FEPE) belonging to the Engineering Faculty of the Ilha Solteira Campus of the Universidade Estadual Paulista (UNESP), located in Selvíria (MS). The treatments consisted of five doses of foliar fertilizer composed of zinc and seaweed extract of Ascophyllum nodosum (0.0; 0.5; 1.0; 1.5 and 2.0 L ha-1) and two situations (absence and presence of A. brasilense (strain Abv5 and 6, at a dose of 1.0 L ha-1), in a randomized block design, with four replicates each treatment. The variables analyzed were plant height, stem diameter, number of leaves, final plant population, dry matter of whole plants, grain and panicle productivity and grain/panicle ratio. From the statistical analysis, it was seen that the fertilizer doses with algae extract were different for the variables dry matter, panicle productivity and grain/panicle ratio, where the control was superior concerning the other doses, mainly for grain productivity. in the presence of Azospirillum brasilense. Thus, the fertilizer with algae extract did not provide significant results in agronomic characteristics, however, the application of the bacteria promoted greater productivity of grains and panicles.